IMPLEMENTASI MODEL PEMBELAJARAN TEAM GAME TOURNAMENT BERBASIS LAGU KREASI TERHADAP HASIL BELAJAR SISWA PADA MATERI PEMANASAN GLOBAL DI MTs NEGERI SINGKAWANG - Ratna Julyanti (EduChem, 2023)
The purpose of this study was to describe the implementation of learning and to determine the magnitude of the increase in student learning outcomes with the Team Game Tournament learning model based on creative songs on global warming material. The subjects in this study were seventh grade students at MTs Negeri Singkawang. The research form used was pre-experimental design. The data collection tools used consisted of pretest and posttest questions. Based on statistical analysis with Wilcoxon, Asymp Sig. obtained 0.000 <0.05 which means that there is an increase in the ability of learning outcomes before and after using the Teams Games Tournament learning model based on Creative Songs. there is an increase in student learning outcomes of 0.54 which is included in the medium category.